Pengaruh SPI, Kepatuhan Peraturan Perundang-Undangan, dan Tindak Lanjut Rekomendasi Hasil Pemeriksaan terhadap Opini Audit BPK. - Nurul Fitria Kamilah; Adam Zakaria; Indah Mulyasari (LPPM IAI Nasional Laa Roiba Bogor, 2024)
The research aimed to obtain empirical evidence regarding the effect of the internal control system, compliance with regulations and laws, and follow-up of audit recommendations on BPK audit opinion. The population of the research is the Ministry and Institution listed in Ikhtisar Hasil Pemeriksaan Semester (IHPS) I 2019 with the observation period during 2016 – 2018. The data was obtained by http://bpk.go.id and Pusat Informasi dan Komunikasi (PIK) BPK RI. The sampling method was performed using the purposive sampling method and obtained 85 samples with the result of 255 observation data. The analysis method was performed using logistic ordinal regression. The result of the research showed that the internal control system has no significant effect on BPK audit opinion. In contrast, compliance with regulations and laws, and follow-up of audit recommendations have a significant effect on BPK audit opinion.